Anti‐inflammatory metabolites from a marine sponge‐associated fungus Aspergillus sp. IMBC‐FP2.05. Issue 1 (29th March 2021) - Quang, Tran Hong; Vien, Le Thi; Anh, Le Ngoc; Ngan, Nguyen Thi Thanh; Hanh, Tran Thi Hong; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Van Minh, Chau
Abstract: Chemical investigation of the marine sponge‐derived fungal strain Aspergillus sp. IMBC‐FP2.05 resulted in isolation of five compounds, including JBIR‐74 (1 ), homogentisic acid (2 ), methyl (2, 5‐dihydroxyphenyl)acetate (3 ), 3‐chloro‐2, 5‐dihydroxybenzyl alcohol (4 ), and p ‐hydroxybenzaldehyde (5 ). Their chemical structures were identified by comprehensive analyses of the 1D and 2D NMR and mass spectra in comparison with the previously reported data. Furthermore, nitric oxide (NO) inhibitory effects of the isolated compounds in LPS‐stimulated RAW264.7 cells were also reported.